2017
DOI: 10.1002/lt.24864
|View full text |Cite
|
Sign up to set email alerts
|

Overt hepatic encephalopathy impairs learning on the EncephalApp stroop which is reversible after liver transplantation

Abstract: After an initial exposure, subjects can develop test-taking/learning strategies called the “test sophistication effect. Cirrhotics wth prior overt hepatic encephalopathy (OHE) could have persistent learning impairments. Aim To define learning/test-sophistication on EncephalApp (downloadable Application) in OHE patients compared to no-OHE patients and controls cross-sectionally and longitudinally. Methods The EncephalApp Stroop App consists of 2 sections; the easier “Off” run assesses psychomotor speed while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Considering this fact, a learning curve may be considered for the reproducibility of the test in order to avoid high rates of false positives as found in our study (50.9%). A previous study had already shown that repeating the test at regular intervals of time is capable of providing better results among cirrhotic patients with no history of CHE (19) ; a similar follow-up in our patients would certainly show the veracity or not of the false positives for the Stroop test. Furthermore, both Stroop and PHES tests aim to evaluate the neurocognitive performance of the patients.…”
Section: Discussionsupporting
confidence: 71%
“…Considering this fact, a learning curve may be considered for the reproducibility of the test in order to avoid high rates of false positives as found in our study (50.9%). A previous study had already shown that repeating the test at regular intervals of time is capable of providing better results among cirrhotic patients with no history of CHE (19) ; a similar follow-up in our patients would certainly show the veracity or not of the false positives for the Stroop test. Furthermore, both Stroop and PHES tests aim to evaluate the neurocognitive performance of the patients.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies in recipients within 18 months posttransplant have documented impairment in visuospatial and executive function. 23 Another cross-sectional study, which examined the cognitive function of 12 liver transplant recipients who survived more than 10 years, also documented the impairment in visuospatial and executive function. 24 Considering the mean time elapsed since transplantation of participants in this study was 7.6 years, our findings suggest that visuospatial and executive function may be part of long-term cognitive decline among individuals with a liver transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the liver–brain axis have been described in liver diseases such as viral hepatitis and liver failure, which lead to a large spectrum of neurological abnormalities. ( 27,28 ) Cognitive impairment in these diseases worsens with age, but significantly improves after liver transplantation, ( 29 ) strengthening the role of the liver in neurological alterations. Numerous reports have emerged describing patients with NAFLD or animal models with cerebral dysfunction and neuropathology similar to AD.…”
Section: Discussionmentioning
confidence: 99%